PELAKSANAAN PERATURAN BUPATI PONOROGO NOMOR 100 TAHUN 2018 TENTANG PERUBAHAN ATAS PERATURAN BUPATI NOMOR 83 TAHUN 2016 TENTANG KEDUDUKAN, SUSUNAN ORGANISASI, URAIAN TUGAS, FUNGSI DAN TATA KERJA BAPPEDA LITBANG KABUPATEN PONOROGO - IFAMA, EKA SILA (Dinamika Hukum, 2019)
The goal of this research is to examine and analyze the implementation of rules of the regent Ponorogo no. 100 year 1018 about the change on the rules of the regent no.83 year 2016 about the position, the formation of organization, job description, function and work schedule of Bappeda Litbang of ponorogo regency also examine and analyze of the obstacles that happened in the implementation of rules of the regent Ponorogo no. 100 year 1018 about the change on the regulation of the regent no.83 year 2016 about the position, the formation of organization, job description, function and work schedule of Bappeda Litbang of ponorogo regency The method of approaching in this research is sociological juridical. Research specification is using descriptive qualitative and data source is using primer data and secondary data. The technique of collecting data is using interview and observation. The technique of analyzing data is using qualitative descriptive analysis. Based on the result of this research it can be got conclusion that the implementation of rules of the regent Ponorogo no. 100 year 1018 about the change on the rules of the regent no.83 year 2016 about the position, the formation of organization, job description, function and work schedule of Bappeda Litbang of ponorogo regency also examine and analyze of the obstacles that happened in the implementation of regulation of the regent Ponorogo no. 100 year 1018 about the change on the rules of the regent no.83 year 2016 about the position, the formation of organization, job description, function and work schedule of Bappeda Litbang of ponorogo regency as follows : 1) the process of communication is held by socializing gradually is ineffective, for the staff that not joined in socializing in the regency area do not understand well. 2) Aspect of resource has been enough amount 53 people, the level education of the staff are Bachelor and Magister in the average, in the case of competition among the staff is still suboptimal. 3). Disposition aspect or attitude of staff that receive and done the regulation of the regent of ponorogo as good as possible, however, to fill the position of functional office planning is not implemented yet for the staff that pointed disagree. 4). Aspect of bureaucratic structure it is Bappeda Litbang of ponorogo regency has owned organization structure, job description and authority of each staff. The obstacles that happened in the implementation of regulation of the regent Ponorogo no. 100 year 1018 about the change on the rules of the regent no.83 year 2016 about the position, the formation of organization, job description, function and work schedule of Bappeda Litbang of ponorogo regency also examine and analyze of the obstacles that happened in the implementation of rules of the regent Ponorogo no. 100 year 1018. There is a rejection from the staff, especially from executive staff as functional office planning. The other obstacles in the implementation of regulation of the regent Ponorogo no. 100 year 1018 that some of the staff still do not master technology of information. Key word : Implementation, Regulation of the Regent of Ponorogo Number 100 Year 2018